Meditasi Sebagai Alternatif Penanganan Stres Psikososial Masyarakat Bali Selama Masa PPKM Darurat - Ida Bagus Putu Adnyana (Jurnal Yoga dan Kesehatan, 2022)
The implementation of Emergency Community Activity Restrictions (PPKM) in Java and Bali as well as other areas in Indonesia that were detected as red zone areas have caused various pros and cons in the community. The implementation of this policy is considered risky because it indirectly causes the community's economic growth to be weak, especially in the area of the island of Bali where the community's source of income comes from the tourism sector. This condition causes not a few Balinese people to experience psychological pressure due to the pressure of high needs while not commensurate with the income they receive. Due to heavy psychological pressure, many Balinese people experience stress and this condition is known as psychosocial stress. Refers to the view of Hinduism this kind of condition can be resolved through the practice of meditation. This study will attempt to discuss the role of meditation as an alternative to handling psychosocial stress in Balinese society during PPKM, which was formulated through several discussions. The discussion includes an understanding of meditation, Balinese psychosocial stress during the Emergency PPKM period, and meditation as an alternative to handling Balinese psychosocial stress during the PPKM period. The method that the researcher uses is descriptive qualitative by collecting, displaying, and analyzing the data that has been obtained based on the document study. As a result, researchers found that meditation can reduce the stress level of Balinese people affected by the Java-Bali Emergency PPKM policy.